Central government role in road infrastructure development and economic growth in the form of future study: the case of Indonesia - Daud Nawir; Muhammad Djaya Bakri; Iif Ahmad Syarif (City, Territory and Architecture, 2023)
Abstract Road infrastructure development in a country has been considered an important predictor of economic development and prosperity. Hence applying a systematic analysis approach, this study aims to project the future role of the central government in developing road infrastructure and its significance in the country's economic growth. The main data sources were the literature review and expert opinions in the form of self-administrative surveys and interviews. Besides, the Cross-impact Direct Influence (CDI) matrix was applied to formulate the questionnaire. For the data analysis purpose, MICMAC analysis and Scenario Wizard software were used. The MICMAC analysis results revealed the dominant role of 9 important/key variables in developing the Indonesian road infrastructure. Simultaneously 24 positive states of the important variables what identified via the Scenario-Wizard Method. Findings also depicted stronger consistency among the four scenarios. Whereas Scenario 1 showed the most ideal 9 key features related to Indonesia’s road infrastructure developments with a high intensity of concentrating the efforts on planning road infrastructure development in big cities and use of smart and modern technology. Moreover, presenting a group of constructs for developing road infrastructure and resultant economic growth in the country, the current study adds value to the existing literature.